Efektivitas Penggunaan Metode Tampung Dan Metode Apung untuk Perhitungan DebitMata Air di Taman Hutan Raya Raden Soerjo (Studi di Blok Prigen Kawasan Rehabilitasi oleh PT. Gudang Garam TBK.): Effectiveness Using Method of Catch and Floating Method for Calculation of Spring Water Debit in the Raden Soerjo Forest Park (Study in Prigen Block Rehabilitation Area by PT Gudang Garam TBK.) - Muttaqin, Tatag; Ardayana, Yhon (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Information on the condition of the springs debit is a decisive aspect in sustainable forest management so that the appropriate method of measuring the flow of a spring shall be known. The formulation of this research problem is the effectiveness of the floating method and the floating method and which method is more effective to be used in the measurement of the spring discharge. How the condition of the existing spring in the rehabilitation area by PT. Gudang Garam TBK Prigen Block Forest Park Raden Soerjo. Methods used in data collection with field observation techniques, documentation, interviews, and questioners based on Antecedent aspects, Implementation aspects and aspects of Outcome. This research was conducted from December 2017 to January 2018 in the rehabilitation area by PT. Gudang Garam TBK Block Prigen Raya Forest Park Raden Soerjo. The results obtained on the aspect of Antecedent in terms of easy procurement tool on the method of catch is quite easy with the scoring interval of 83.33% and floating method is very easy with scoring interval 76.67%. The cost of procurement tool is a very cheap method of catch with scoring interval 85,56% and cheap floating method with scoring interval 73,33%. The result of the measurement of the springs debit on the Implementation aspect is the method of the catch has a working performance of 4.85 springs/hour and the floating method has a working performance of 4.65 springs/hour. The data processing of springs debit using the method of the catch has a working performance of 62.57 springs/hour data and floating method has a working performance of 48.59 springs/hour data. The result on the outcome aspect of the difference of the measurement result of the debit method of catch is slightly having the interval score of 77.78% and the floating method has an interval score of 68.89%. Around the study site, there are six springs namely the water of Kubisan 1, Kubisan 2, Alap-Alap, Grojokan Pring 1, Grojokan Pring 2 and Jeding Pendem. The measurement of the discharge of spring water using the catch method is generally more effective than the floating method so that the use of the catchment method in the measurement of the spring discharge is preferred. The condition of the springs based on observations has a good physical condition.